A review of the macrochelid mites of Turkey (Acari: Macrochelidae), with new records and descriptions of three new species - Özbek, Hasan Hüseyi̇n (Zootaxa, 2017)
This study reviews the family Macrochelidae in Turkey, with new information about species diversity. Nothrholaspis scutivagus sp. nov., Macrocheles niksarensis sp. nov. and Holostaspella bidentata sp. nov. are described as new species from Turkey. Nothrholaspis scutivagus has a characteristic dorsal shield chaetotaxy, and post-genital platelets that are sometimes fused to the ventri-anal shield. Macrocheles niksarensis has 29 pairs of pilose dorsal shield setae and a machete-like cheliceral dorsal seta. The genus Holostaspella is recorded from Turkey for the first time, on the basis of H. bidentata. Macrocheles peniculatus and M. insignitus are reported from Turkey for the first time. Also, Macrholaspis recki and M. evansi are presented here with some notes on the Turkish specimens.